Sustainable nitrogen solutions: Cyanobacteria-powered plant biotechnology for conservation and metabolite production - Taufiq Nawaz; Shah Fahad; Shah Saud; Ruanbao Zhou; Nader R. Abdelsalam; Mohamed M.A. Abdelhamid; Mariusz Jaremko (Current Plant Biology)
As photosynthetic microorganisms, cyanobacteria play a dominant part in numerous ecological systems owing to their ability to fix carbon and nitrogen and are therefore an essential part of primary production in both aquatic and terrestrial environments. The utility of nitrogen-fixing cyanobacteria in plant biotechnology opens up promising strategies for the conservation and sustainable use of rare, endangered plant species and bioactive cell cultures. Here, we discuss the complicated physiological aspects of biological nitrogen fixation in cyanobacteria and their symbiotic relationship with plants. This review focuses on recent advances in biotechnological tools such as CRISPR-Cas9, nanotechnology and multiomics-based approaches for enhancing plant regeneration systems to cultivate specialized metabolites. We also look at the methods in vitro preservation of plants and how to scale up a culture using bioreactor systems. The review ends by highlighting the promise of cyanobacteria-powered plant biotechnology as a renewable mechanism for rare species conservation and specialized metabolites production, providing an optimistic modal, formative future direction in plant biosynthesis.